ESENSI HUTANG DALAM KEUANGAN RUMAH TANGGA YANG ISLAMI - Mohammad Agus Nugroho (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Debt is permissible in Islam, but debt can bring a person to heaven because of his intention to please help his fellow human beings (hablun minannaas), debt can also bring a person into the fire of hell when not managed properly. So the debt becomes the last alternative is not the first done if the household finances are not stable. Financial management with the corridor of the fulfillment of the benefit can reduce the risk of household financial instability, by making family financial planning aimed at achieving falah (prosperous world and the hereafter), avoiding maisir ways, gharar, riba and unjust both in collecting income and in spend it, give priority to sadaqah even though rizki is narrow, and away from nature wasteful.